Optimization framework for cost and carbon emission of timber floor elements. (1st February 2022) - Nesheim, Sveinung; Mela, Kristo; Malo, Kjell Arne; Labonnote, Nathalie
Highlights: Optimisation of cost and ECO2 for timber floor elements for adaptable buildings. Mixed-integer sequential linearization combined with parametric manufacture accounting. Optimisation model used to analyse the characteristics of the optimum designs. A comparison between the current and the second generation of Eurocode 5. Extensive combinations of structural typologies and outfitting subject for optimisation. Abstract: Long-span timber floor elements increase the adaptability of a building and they exhibit a significant market potential. High cost of the floor elements is a challenge, and the timber sector is under substantial pressure to find more economical solutions without weakening otherwise favourable environmental performance. The range of technical timber-based materials and components, structural typologies, overlays and ceiling systems represent an immense solution space when searching for a competitive design for a specific building application. Finding the optimum solution requires a computational procedure. In this study a recent development for the accounting of manufacturing resources for timber elements is utilized to build an optimization framework for cost and ECO2 minimisation of timber floor elements finalized at the factory gate. The design of the element is formulated as a discrete optimization problem which is solved by a mixed-integer sequential linearization procedure. Various material combinations and constraint combinations are treated. The optimization framework provides a tool for rapid design exploration that can be used in timber floor design situations. The results of the calculations carried out in this study provide insight on the general trends of optimum floor elements. The optimization model is used to analyse the characteristics of the optimum designs, and a comparison between the current and the proposed method for the second generation of Eurocode 5 is chosen as a vehicle for demonstrating achievable implications.